1996
DOI: 10.1002/masy.19961010153
|View full text |Cite
|
Sign up to set email alerts
|

The surface and interfacial chemistry of polyimide films

Abstract: The surfaces of polyimide films and the structure just below the surfaces have been extensively studied as people have sought to improve and understand the key factors controlling adhesion. Treatments of all types from primers to plasma etching to sand blasting have been evaluated with varying efforts depending on the application. In recent years, the emphasis has been on understanding the chemical and morphological changes effected by these treatments and then correlating chemistry and morphology with adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The interest in these polymers arises from their technological importance, based on their high thermal and chemical stability, together with their low-k dielectric and other desirable properties. [8][9][10][11][12][13] Polyimides have found widespread large-volume use as insulators but are also widely employed as low-k dielectrics in the device industries and as the substrate of choice for liquid-crystal displays. 8,14 Polyimides are readily formed both in solution and in the solid state by a condensation reaction between a dianhydride and a diamine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interest in these polymers arises from their technological importance, based on their high thermal and chemical stability, together with their low-k dielectric and other desirable properties. [8][9][10][11][12][13] Polyimides have found widespread large-volume use as insulators but are also widely employed as low-k dielectrics in the device industries and as the substrate of choice for liquid-crystal displays. 8,14 Polyimides are readily formed both in solution and in the solid state by a condensation reaction between a dianhydride and a diamine.…”
Section: Introductionmentioning
confidence: 99%
“…18,37 The properties of the polyimide film interface, with the substrate on which it has been deposited, are important for many applications, relating as they do to adhesion and film growth characteristics. 9 There have, however, been rather few studies of PI growth from vapour deposited precursors in the coverage range from submonolayer, through monolayer to a few monolayers. [18][19][20][21]23,26 Some studies have suggested that order found within thin films is reduced at the surface 25,34 and vibrational spectroscopies have indicated a higher percentage of the iso-imide species arising from a minor side reaction of the precursor molecules.…”
Section: Introductionmentioning
confidence: 99%